A systematic review of professional reasoning literature in occupational therapy. (January 2016) - Unsworth, Carolyn; Baker, Anne
Introduction: Over the past 33 years, theoretical and empirical articles have been published on professional reasoning in occupational therapy. This systematic review sought to answer two questions: (1) What is the nature and volume of professional reasoning literature; and (2) What do we know about the development of professional reasoning in students through literature exploring novice and expert differences? Method: A systematic review of the peer-reviewed literature with narrative and critical analysis. Findings: A total of 140 articles were classified into six topic areas: what is professional reasoning, ethics and moral reasoning?, methods of studying professional reasoning, novice–expert differences, professional reasoning of assistants, and advancing specific fields of practice using professional reasoning. Of these, 68% included analysis of data, and the remainder were discussions. Fourteen articles examining novice–expert differences were critiqued but only eight were rated as strong. Research findings prompt the need for reflection, extended fieldwork, and development of protocols to facilitate reasoning. Conclusion: This is the first systematic review of the professional reasoning literature, and provides a foundation for more detailed critiques of specific topics to be undertaken. While research strengths have been identified, gaps include the use of standardised measures of professional reasoning and identification of educational approaches that promote professional reasoning.